Identification of a Risk Profile for New-Onset Diabetes After Acute Pancreatitis. Issue 5 (May 2021) - Firkins, Stephen A.; Hart, Phil A.; Papachristou, Georgios I.; Lara, Luis F.; Cruz-Monserrate, Zobeida; Hinton, Alice; Conwell, Darwin L.; Bradley, David P.; Krishna, Somashekar G.
Abstract : Objectives: There is a paucity of studies evaluating predictors of new-onset diabetes mellitus (DM) after acute pancreatitis (AP-related DM). We used a population-based database to evaluate predictors of AP-related DM. Methods: The Nationwide Readmissions Database (2010–2014) was used to identify all nondiabetic adults with an index primary diagnosis of AP. Multiple exclusions were applied to identify cohorts with and without AP-related DM. A case-control study was conducted to identify risk factors for developing AP-related DM within the calendar year. Results: We identified 2510 subjects with AP-related DM and 40, 308 controls with AP who did not develop DM. Multivariable analysis revealed that increasing age (50–64 years; adjusted odds ratio [aOR], 1.35; 95% confidence interval [CI], 1.14–1.60), male sex (aOR, 1.2; 95% CI, 1.03–1.40), lowest income quartile (aOR, 1.48; 95% CI, 1.18–1.84), Elixhauser comorbidity index of 3 or higher (aOR, 1.47; 95% CI, 1.23–1.75), components of metabolic syndrome (aOR, 2.12; 95% CI, 1.21–3.70), severe AP (aOR, 1.60; 95% CI, 1.34–1.90), and recurrent AP (aOR, 1.46; 95% CI, 1.24–1.72) were independently associated with increased risk of AP-related DM. Conclusions: These population-level variables predictive of developing AP-related DM can potentially identify patients who may benefit from closer follow-up, intensive education, and implementation of preventative strategies. Abstract : Supplemental digital content is available in the text.